FENOMENA PENGGUNAAN BAHASA GAUL DALAM KEHIDUPAN SOSIAL REMAJA BALI DI KELURAHAN SESETAN, KOTA DENPASAR - Aditya, Wasu; Suka Arjawa, I Gusti Putu Bagus; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2021)
Phenomenon of the widespread use of slang has unwittingly brought a new social structure into the social order of society, including the life of the Balinese people, where the Balinese already have their own social structure that regulates the social order of their society. This research was conducted to find out the various factors that encourage the entry of slang into the Balinese youth environment, and what impact this slang phenomenon has on social life and Balinese society. The theory used in this study is the theory of Structuralism from Levi-Strauss. The impact generated by the new social structure can produce negative or positive impacts according to the views of each individual, but a deep understanding of the causes and effects of the resulting impacts will be more open-minded about the use of the old structure or the new structure in carrying out the social order of Balinese society. Keywords: Slang, Structuralism, Sor Singgih Basa Bali, Social Structure.